The Need of Distance Learning in the Wake of COVID-19 in Morocco: : Teachers’ Attitudes and Challenges in the English Foreign Language Instruction - Bachiri, Housseine; Sahli, Rabha (International Journal of Language and Literary Studies, 2020)
Owing to the rapidly ubiquitous infection of Coronavirus in Morocco and other parts of the globe, a plethora of governments have urgently resorted to implement distance learning to save the current academic year from an evitable failure. Given the non-prevalence of information and communication technologies (ICTs) in Morocco, distance learning has been a quite bold attempt to officially continue education, even after the closure of schools and campuses, without interruption with a slightly adjusted grading scale in order to lead the boat of the current academic year to a safe harbor. In this regard, many underprivileged students have benefitted from free modems and laptops, the case of Euromed University of Fes (UEMF). This great initiative has enabled the aforementioned students to enjoy the full experience of distance learning. As for secondary schools and most public institutions, the supply of electronic devices has almost been lacking. One should know that the government has taken some modest initiatives, such as offering free access to a few platforms, national channels, and official pages of the aforesaid ministry, namely TelmidTICE. It must be noted that distance learning, in Morocco, has continuously undergone various challenges during COVID-19 ranging from content and pedagogy to assessment and evaluation. Having used both quantitative and qualitative research for the purpose of gathering relevant data by means of questionnaire and participant observation, we have been able to ferret out the real challenges that are structurally embedded and ramified in the application of distance learning whose infrastructure must be constantly buttressed via empirical research and quality teacher training to better respond to different learning needs and styles, and simultaneously combat digital illiteracy.